Labor Market Deregulation and Female Employment: Evidence from a Natural Experiment in Japan - Takao Kato; Naomi Kodama (Institute for the Study of Labor (IZA), 2014)
This paper provides novel evidence on the causal effect on female employment of labor market deregulation by using the 1985 amendments to the Labor Standards Law (LSL) in Japan as a natural experiment. The original LSL of 1947 prohibited women from working overtime exceeding two hours a day; six hours a week; and 150 hours a year. The 1985 amendments exempted a variety of occupations and industries from such overtime restriction on women. We first define "jobs" using an industry by occupation matrix. For each job (close to 5,000 jobs in total), we carefully identify whether or not it was made exempt from the overtime restriction on women by the 1985 amendments. Applying a difference-in-difference model to census data, we find a statistically significant and economically meaningful impact on female employment of this particular piece of labor market deregulation. Furthermore the 1985 treatment is found to have a lasting and growing impact on female employment. Our finding is consistent with the recent literature that points to the importance of paying particular attention to the issues surrounding working hours when policymakers design public policy to promote female employment.
Keywords: J16; J78; J81; J82; J88; 330; female employment; labor market deregulation; natural experiment; overtime restriction on women; Labor Standards Law